PENGARUH HARGA, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TEH SIAP MINUM DALAM KEMASAN TEH BOTOL SOSRO (Studi Kasus pada Mahasiswa S1 Fisip Undip Semarang) - Venia Afrilia Sari; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The main needs such as food and beverages are necessities that must be met. In thisfast-paced era, humans need everything easy and practical, especially drinks. This resulted inmany companies in Indonesia competing to produce soft drinks in packaging. Therefore,every business must be able to increase sales in order to survive in this business world. Inparticular, this study discusses the purchase of Tea Ready Drinking In Packing brand TehBotol Sosro Semarang which during the year 2012-2016 decreased sales. If it is not repairedand resolved is not impossible will cause problems for PT. Sinar Sosro Semarang in thefuture.Aim of this research was to found of price, quality and brand image on purchasing decisionsof Tea Ready Drink In Packaging Teh Botol Sosro on consumers Student S1 Faculty of Social andPolitical Sciences Diponegoro University Semarang. Type of research used is eksplanatory research.The samples used are 100 respondents who consume of Teh Botol Sosro. The sampling techniqueused is Purposive Sampling. Methods of data analysis using correlation test, determination test,simple linear regression test, multiple linear regression test, t test and f test with the help of IBMSPPS (Statistical Product and Service Solutions) program version 16.0.Based on the analysis results concluded that price, product quality and brand imagehave a positive effect on purchasing decision. Significantly, price variables, product qualityand brand image have a positive effect on purchasing decisions. There are some indicatorsthat are still below average, suggestions given to the company is to megevaluasi pricecompetitors, re-evaluate the quality of its products and maintain its brand image.